2021
DOI: 10.3390/ijms22083841
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role for Fructosamine-3-Kinase in Cataract Treatment

Abstract: Cataracts are the major cause of blindness worldwide, largely resulting from aging and diabetes mellitus. Advanced glycation end-products (AGEs) have been identified as major contributors in cataract formation because they alter lens protein structure and stability and induce covalent cross-linking, aggregation, and insolubilization of lens crystallins. We investigated the potential of the deglycating enzyme fructosamine-3-kinase (FN3K) in the disruption of AGEs in cataractous lenses. Macroscopic changes of eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…Maximal effects on lens opacity are observed in the wavelength range of 410–430 nm, which is a typical absorbance wavelength of Maillard products that induces a yellow-brownish coloration of aged lenses. Our observations strengthen our hypothesis that the process of non-enzymatic glycation of proteins such as crystallins can be reversed [ 11 , 20 ]. Several studies have demonstrated that Maillard reactions involving sugars can induce a decrease in the chaperone function of α-crystallins [ 22 , 23 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Maximal effects on lens opacity are observed in the wavelength range of 410–430 nm, which is a typical absorbance wavelength of Maillard products that induces a yellow-brownish coloration of aged lenses. Our observations strengthen our hypothesis that the process of non-enzymatic glycation of proteins such as crystallins can be reversed [ 11 , 20 ]. Several studies have demonstrated that Maillard reactions involving sugars can induce a decrease in the chaperone function of α-crystallins [ 22 , 23 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 88%
“…AGE-inhibiting or -disrupting compounds may be effective at preventing and treating AGE-related processes. FN3K has been shown to reverse crystalline glycation in cataracts [ 11 ]. This process eventually prevents AGE formation.…”
Section: Introductionmentioning
confidence: 99%
“…22 Some scholars believe that AGEs, duration of DM and the level of blood glucose control play an important role in the occurrence and development of this disease. 23,24 In our study on diabetic patients including a significantly larger cohort, we found that the content of AHG and AGEs in AH from patients with prolonged diabetes and poor blood glucose control was higher than that from patients with short-term diabetes and good blood glucose control. We also found a strong positive significant correlation between AHG and AGEs levels with a Pearson coefficient constant R = 0.540 (significance at the 0.01 level).…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, it would be interesting to see if a correlation between FN3K and GNEM could be found—as it exists, for example, in relation to diabetes mellitus [ 155 , 156 ]. A recent study investigating the effect of ex vivo intravitreal FN3K injections on AGE-based cataracts seems to be quite promising as a potential new treatment of certain types of cataracts [ 157 ]. Therefore, it might be good to see if glucose-derived glycation products play a role in GNEM and whether activating the FN3K in muscle cells—maybe it might be possible to inject FN3K-solutions directly into the muscle (i.m.…”
Section: Discussion and Outlookmentioning
confidence: 99%